Annotated bibliography about Asian martial arts monographs published in Spain - Mikel Pérez-Gutiérrez; Carlos Gutiérrez-García; Eduardo Álvarez del Palacio (Universidad de León, 2013)
Aim: The aim of the present study was to create an annotated bibliography of all Asian martial arts monographs published in Spain until 2009. Method: Main national and international databases, martial arts bibliographies as well as the own Asian martial arts monographs were used for data mining. The documentary analysis of monographs, the presentation of references and the preparation of the bibliography structure was determined by UNE 50-104-1994, UNE 50-103-1990, UNE 50-121-1991 rules together with the previous work developed by the authors. Results/Conclusions: A total number of 1.564 bibliographic entries, referring to 2.403 editions of martial arts monographs were obtained. These references were grouped in 17 categories and 40 subcategories. The present study has gathered more than a century of history of martial arts monographs, becoming a reference work for academics and martial arts fans.